Adult sage‐grouse numbers rise following raven removal or an increase in precipitation - Luke W. Peebles; Michael R. Conover; Jonathan B. Dinkins (Wildlife Society Bulletin, 2017)
ABSTRACT Weather and lethal control of common ravens (Corvus corax; hereafter, ravens) can affect the nesting success of greater sage‐grouse (Centrocercus urophasianus), but implications of these effects in terms of the subsequent size of the breeding population are unknown. We used generalized linear mixed models to assess the effects of weather and raven removal on sage‐grouse lek trends within Wyoming, USA, from 2008 to 2015 by counting male sage‐grouse at leks within 8 circular sites each with a 16‐km diameter and 4 circular sites with a 24‐km diameter. We compared sites where U.S. Department of Agriculture/Animal and Plant Health Inspection Service Wildlife Services (WS) removed ravens the previous year (removal sites) with other areas where they did not (nonremoval sites). Wildlife Services intensified removal efforts beginning in 2012; and, 1‐year later, WS started removing ravens to benefit sage‐grouse (i.e., raven removal was conducted near prime nesting habitat for sage‐grouse). Raven densities decreased 50% from 2008 to 2014 in removal sites, but increased in nonremoval sites by 42% based on 6,255 point counts conducted at 1,154 random locations. We hypothesized that adult sage‐grouse numbers would be greater at the 30 leks in removal sites compared with the 28 leks in nonremoval sites. The top AICc model showed that the percent change in raven numbers, minimum temperatures during the brood‐period, and precipitation during the brood‐period were informative predictors of lek counts during the next year. Fewer ravens, cooler temperatures, and more precipitation were associated with more adult males on leks. Cooler temperatures and more precipitation probably increased the survival of sage‐grouse chicks indirectly by increasing their forage, while a decrease in raven numbers may have increased nest success rates. This study was one of the first to demonstrate a positive correlation between these variables and changes in the number of adult male sage‐grouse on leks in the subsequent year. © 2017 The Wildlife Society.